URGENSI PENYELESAIAN PERMASALAHAN HUMANTRAFFICKING TRANSNEGARA SEBAGAI UPAYA PENEGAKANHUKUM DAN PERLINDUNGAN KORBAN HUMAN TRAFFICKING - Saragi, Paltiada (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Human Trafficking is a criminal act that has the potential to be committed across national borders. This makes the issue of which country has the authority to punish suspects of Human Trafficking difficult because of the overlap between the principles of territoriality and the principle of personality in criminal law. International law should have an active role in answering issues that cannot be resolved independently by countries alone without international legal instruments. Criminal law clearly recognizes that there is a universal principle for enforcing criminal law. The recognition and need for international law then creates an urgency for the creation of an international organization that specifically focuses on eradicating Human Trafficking. This need is part of the role of international law that equalizes the position of countries so that there is no egocentrism regarding the punishment of suspects of Human Trafficking which is dualistic.